Inclusive and gender-transformative seed systems - Galie, Alessandra; Kawarazuka, Nozomi; Rietveld, Anne; Kramer, Berber; Shikuku, Kelvin Mashisia; Andrade, Jorge; Marshall, Karen; Lillesø, Jens-Peter Barnekow; Ragasa, Catherine; McEwan, Margaret; Yila, Jummai; Spielman, David J.; et al. (2021)
Lead authors: Alessandra Galie; Nozomi Kawarazuka; Anne Rietveld; and Berber Kramer Co-authors: Kelvin Mashisia Shikuku; Jorge Andrade; Karen Marshall; Barnekow Lillesø Jens-Peter; Catherine Ragasa; Margaret McEwan; Jummai Yila; David Spielman; Isabelle Baltenweck; and McDougal Cynthia